Solute-vacancy interactions in Cu and Ag - N. Stefanou; N. Papanikolaou; P.H. Dederichs (Journal of Physics: Condensed Matter, 1991)
The authors present local-spin-density-functional calculations for the interaction energies of vacancies with 3d and 4sp impurities in Cu as well as with 4d and 5sp impurities in Ag. The calculations are based on the jellium model and first-order perturbation theory, thus enabling an interpretation of the interaction in purely electrostatic terms. The results are in agreement with those obtained by first-principles calculations and confirm the experimentally known trends.